The Effect of Financial Literacy and Self-Control on Saving Behavior of Students of Muhammadiyah University of Palopo - Melisa; Asriany; Andika Rusli (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of financial literacy and self-control on the saving behavior of students at the University of Muhammadiyah Palopo. The type of research conducted in this study is quantitative, by distributing questionnaires online to 97 student respondents. The sampling method used in this study is the purposive sampling technique where the determination of the sample is carried out with special considerations. The data used in this study are primary data, taken from respondents using questionnaires. The data analysis method in this study is multiple linear regression using the SPSS 26 application. The results of the t-test show that financial literacy has a significant influence on saving behavior and self-control has a significant influence on saving behavior. The results of the F test show that there is an influence between the independent variables of Financial Literacy and Self-Control simultaneously on the dependent variable of Saving Behavior.